Transient heat conduction across thermal barrier coating on an anisotropic substrate. Issue 3 (2014) - Y.M. Lee; T.W. Tsai; Y.C. Shiah
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to examine the transient heat conduction in a two‐dimensional anisotropic substrate coated with a thin layer of thermal barrier coating (TBC). Nowadays, materials with anisotropic properties have been extensively applied in various engineering applications for enhanced strength. However, under an extreme operating environment of high temperature, the strength of the materials may largely decline. As a common practice in engineering, TBC are usually applied to thermally insulate the substrates so as to allow for higher operating temperature. This research provides engineers a numerical approach for properly designing the TBC to protect the anisotropic substrate. Design/methodology/approach – For this investigation, a finite difference scheme using the domain mapping technique, transforming the anisotropic domain into isotropic one, is employed. The analysis considers three respective boundary conditions, namely Dirichelete condition, Neumann condition, and also forced convection, and studies the effect of various variables on the heat conduction in the coated system. Additionally, formulas for the steady‐state temperature drop across the coating layer at the center are analytically derived. By comparing the numerical results with the analytical solutions, the veracity of the formulas is verified. Findings – A few interesting phenomena are observed from the numerical results. First, the rotation of the substrate's principal axes affects the temperature on the TBC front surface in a more obvious manner for the Neumann condition than that for convection. Second, the temperature profile of the Dirichelete condition rises faster than the other cases, although all their profiles present a similar pattern. Third, the transient temperature drop across the TBC under the convection condition presents a complicated pattern, depending on the TBC thickness. Finally, the increase of TBC thickness under the Dirichelete condition may provide better insulation than the other cases. In this paper, approximate analytical formulations for the steady‐state temperature drop across the TBC are also presented. Numerical results by the finite difference method indicate excellent agreements with the analytical solutions. Originality/value – In the past, the finite element method (FEM) is usually applied for analyzing the heat conduction problem of TBC. However, one serious deficiency of applying the FEM to the TBC problem lies in the demand for a vast amount of elements (or cells) when the TBC thickness is far smaller than the substrate dimension. For ultra‐thin coating, an enormous amount of elements are required that may lead to an extremely heavy computational burden. The paper presents an innovative finite difference approach that can be applied to analyze the heat conduction across the TBC coated on an anisotropic substrate. On the interface between the TBC and the substrate, a special heat equilibrium condition and the compatibility condition of identical temperature on the adjacent materials are used to propose three new models to predict the temperature drop across the TBC. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors would like to express great gratitude to the National Science Council of Taiwan for the financial support (101‐2221‐E‐035‐008 and 99‐2221‐E‐035‐027‐MY3). </ack>